‘When something doesn’t fit the story’: human suspicion and discretion in frontline border checks in times of datafication and technologisation - Fabritius, Nora (Policing and society, 2024)
In this article, I ask how Finnish border guards negotiate their role as human decision-makers in frontline border checks in the current era of datafication and technologisation. I address this question by delving into the key decision made in frontline border checks: namely, whether to let travellers pass or to send them for further inspection. This decision is pivotal in the sorting of people crossing borders, that is, who is admitted, who is held up, and who is turned away. Through an analysis that borrows from Institutional Ethnography and argumentation analysis, based on interviews with border guards and observation at the Border and Coast Guard Academy, I show that even as security authorities are seeking to increase the use of technologies and automation, Finnish frontline border guards present their own discretionary powers as unchallenged by technology and automation and argue that human feelings, senses, and experience are key to the formation of suspicion at the border. Storytelling is placed at the centre of the decision-making process, in which suspicion is directed at those whose stories do not ‘fit’ or ‘feel right’. Border guards locate their professional skill and worth in their discretionary powers, manifested in their human ability to evaluate the entity of the ‘story-human’: the body, the story, the documents, and the setting. Data systems and technology only offer pieces. These insights exemplify how law translates into the sorting of humans at borders and can also guide future studies of street-level bureaucrats re-orienting in an increasingly automated world.